Komunikasi Antar Budaya Santri di Lingkungan Pondok Pesantren Nurul Hidayah Jember - Widya Sari; Minan Jauhari (Fakultas Dakwah UIN KHAS Jember, 2022)
Intercultural communication between students at the Nurul Hidayah Islamic boarding school Jember is faced with various problems both in terms of language, such as misunderstandings in understanding the meaning of language, until differences in nonverbal meanings such as speech intonation, how to dress to body movements. The focus of this research is to examine the process of verbal and nonverbal communication between students with different cultural backgrounds at the Nurul Hidayah Islamic Boarding School. The purpose of this study was to determine the process of verbal and nonverbal communication between students with different cultural backgrounds at the Nurul Hidayah Islamic Boarding School. method used is qualitative with a descriptive approach. The technique of collecting data is through observation, interviews, and documentation. The results of this study were obtained with conclusions, namely: 1) Verbal communication used is language. The use of the majority regional language that students use is Javanese, by using Javanese, the students' intercultural communication becomes more near than using Indonesian. That way, there is an effort for immigrant students to learn the Javanese language in order to avoid barriers to intercultural communication. The students also know each other's language in their respective regions in order to avoid misunderstandings in understanding the meaning of a word if it is interpreted in the language of each student's area. Various nonverbal meanings when conducting intercultural communication can be seen through the intonation when speaking, the body language of students and the way students dress. The difference in speaking intonation that comes from the accent of a region, is able to create stereotypes for a santri. These stereotypes become obstacles in communicating between cultures. To avoid this, it is necessary to have ethics behavior by students of different cultures, such as not creating stereotypes against an ethnicity, and respecting other cultures.